Purified Human Plasma Kallikrein Does Not Stimulate but Primes Neutrophils for Superoxide Production - Zimmerli, Werner; Huber, Isabelle; Bouma, Bonno N; Lämmle, Bernhard (Thrombosis and Haemostasis, 1989)
In patients with septicemia and septic shock the contact phase of blood coagulation is activated. It has been suggested that polymorphonuclear leukocytes (PMN) are directly activated by purified plasma kallikrein. This has been recently questioned because granulocytic elastase release induced by recalcification of normal and prekallikrein-deficient plasma was similar. We studied the interaction of different preparations of purified human plasma kallikrein with PMN. Cytosolic calcium shifts were measured with the quin2 method, PMN aggregation was assayed in an aggregometer, and superoxide production was quantitated as superoxide dismutase inhibitable cytochrome c reduction in a continuous assay. No increase of cytosolic free calcium was found during at least 5 min after adding 10 μg/ml plasma kallikrein to PMN. Similarly, highly purified plasma kallikrein from two different sources did not induce PMN aggregation at all, nor did it stimulate superoxide production. However, sequential exposure of PMN to plasma kallikrein and formylpeptide increased the superoxide production compared to stimulation with formylpeptide alone. This phenomenon which is called priming was observed at plasma kallikrein concentrations ≥7 μg/ml. The active site of the molecule was required for the priming, because plasma prekallikrein, active site-inactivated plasma kallikrein, and soybean trypsin inhibitor treated kallikrein did not prime PMN. This indicates that the contact activation system may play a role in host defence against bacterial infection.
Keywords: Neutrophils; Kallikrein; Priming